Studi Habitat Ikan Gelodok (Boleophthalmus sp.) Di Kawasan Ekowisata Hutan Payau, Tritih Kulon, Kabupaten Cilacap Berdasarkan Kandungan Total Nitrat Dan Total Fosfat - Dewi Wisudyanti Budi Hastuti; Anita Putri Setiyaningrum; Hendrayana Hendrayana; Rivani Rivani; Anandita Ekasanti; Emyliana Listiowati; Dewi Nugrayani (Jurnal Perikanan Unram, 2024)
The mangrove ecosystem in the Brackish Forest Area, Tritih Kulon, Cilacap, is affected by various human activities, which cause an increase in total nitrate and phosphate concentrations in the waters. Nitrates and phosphates are essential nutrients that support the growth and survival of organisms. This research aims to measure total nitrate and phosphate levels, and relate them to the suitability of mudskipper habitat in the area. The research was carried out using descriptive methods, using water and sediment samples from the mudskipper habitat. Water quality is measured through parameters such as temperature, salinity, and dissolved oxygen (DO). The results showed that the total nitrate concentration in water ranged from 2.35 to 3.65 mg/L with an average of 3.12 mg/L, while in sediment it ranged from 1.02 to 1.85 mg/kg with an average of average 1.4 mg/kg. The total phosphate concentration in water is in the range of 0.6 to 0.94 mg/L with an average of 0.81 mg/L, while in sediment it ranges from 0.94 to 1.45 mg/kg with an average of 1, 22 mg/kg. Keywords: Habitat, Mudskipper, Total Phosphate, Total Nitrate